Performance Characterization for Polymer Modified Bitumen Contained Newly Used Terpolymer - Chafat, Osamah H.; Al-Humeidawi, Basim H.; Abed, Alaa H. (Civil Engineering Journal, 2025)
Polymer-modified bitumen (PMB) plays a vital role in extending the service life of hot mix asphalt (HMA) used in flexible pavement construction. Several types of polymers have been used to produce PMB, among which styrene–butadiene–styrene (SBS) is the most widely used. However, the use of SBS in PMB production presents several limitations, including storage stability issues, high mixing temperatures, and the requirement for a relatively high modifier content. The present research investigated the use of a new terpolymer, EVA-GMA (LOTADER® AX8670T), for PMB production and compared the resulting PMB with PMB produced using 4% SBS polymer. Rheological, performance, and chemical composition tests were conducted on neat bitumen as well as PMB modified with EVA-GMA and SBS. The results indicated that the optimal LOTADER® AX8670T content required to produce PMB was 2.5%. In addition, storage stability increased by 11% compared to 4% SBS-modified PMB. The viscosity was found to be 50% higher than that of asphalt modified with 4% SBS-PMB and 100% higher than that of unmodified asphalt. The performance grade (PG) was determined to be PG 82-10 for both PMB types, while unmodified bitumen exhibited a PG of 76-10. Based on these results, it can be concluded that PMB produced with LOTADER® AX8670T can perform comparably to SBS-modified PMB while requiring a lower modifier content, lower mixing temperatures, and offering improved storage stability, thereby enhancing economic, production, and environmental aspects.